The Movement of Al-Mukhtar ibn Abi Ubayd al-Thaqafi in Kufa (64 AH - 67 AH / 684 - 686 AD) Between Discourse, Slogans and Political Position - Haj Yasen, Riad Hammoudeh; Al-Faouri, Amjad Mamdouh (Jordan Journal for History and Archaeology, 2026)
The study examines analytically the movement of al-Mukhtar ibn Abi Ubayd al-Thaqafi in terms of its rhetoric and slogans. This movement emerged in Kufa in opposition to Umayyad rule and was distinguished by its political positions centered on demanding retribution for the killers of al-Husayn ibn ‘Ali and asserting the right of his brother Muhammad ibn ‘Ali ibn Abi Talib, known as Ibn al-Hanafiyah (d. 81 AH / 700 CE), to the imamate. This movement played political and military roles that deepened the Shi‘i revolutionary discourse opposing the Umayyad state and, ultimately, established a new trend in Shi‘i thought characterized by extremism, fanaticism, and revolutionary zeal. Accordingly, the study seeks to elucidate the intellectual and cultural rhetoric of al-Mukhtar’s movement, especially by examining the slogans it adopted and how they were reflected in the positions it promoted.